Consumer creativity and the world's biggest brand. (1st January 2014) - Plangger, Kirk; Robson, Karen
There are many ways that consumers can be creative with products and services, however not all creations are made with equal creativity. Fifty-one consumer generated uses for Coca-Cola are evaluated on the two dimensions of creativity: novelty and utility. These dimensions form a four-category typology of consumer creativity: low value uses, marketed uses, unusual uses, and potentially marketed uses. Each of these types presents a unique set of risks and opportunities for brands and firms. Implications for how a firm may respond to these risks and opportunities are discussed.